Organizational Citizenship Behavior (OCB) dan Pengaruhnya Terhadap Keinginan Keluar dan Kepuasan Kerja Karyawan - Agus Triyanto; Te Elisabeth Cintya Santosa (Jurnal Manajemen Maranatha, 2009)
This study will investigate how relation among OCB within turnover intention and job satisfaction is and also how is the influence of OCB toward two of those attitudes. The samples of the research are 102 Police members in state “X” in West Java, by purposive sampling. The examination utilizes with simple regression analysis. The result showed that there is no negative significant relation and influence between OCB and turnover intention, but positive significant relation and influence between OCB and job satisfaction.